Depression Reduction Among Acupuncture Patients in an Interprofessional Study. (March 2020) - Leung, Patrick; Cheung, Monit; Hou, Liwen; Webb, Ann E.; Chen, Xin; Hune, Nikki
Purpose: Acupuncture as a sole treatment was tested for patients with depressive symptoms when seeking treatment in an interprofessional project. This study aims to test the relative effects of depression-specific acupuncture treatment (DSAT) versus nondepression-specific acupuncture treatment (Non-DSAT) on depression scores of patients seeking acupuncture care. Method: In this chart-review quasi-experimental study, former patient charts were randomly selected from a 3-year record at two college-operated acupuncture clinics in Houston. Among them, 62 charts contained depression data measured by the Hopkins Symptoms Checklist-25 (HSCL-25). Results: Data show that 39 patients received DSAT and 23 patients received Non-DSAT, but none of them indicated depression as a reason for treatment. After treatment, although the prevalence rate was lower, the average depression score was higher in both groups. Further analysis with the mixed between-within-subjects analysis of variance showed insignificant group interactive effects on the depression score change. Discussion: Depression outcomes between the two groups were not conclusive. Acupuncture as a depression treatment method should be further tested with a longitudinal research design focusing on patients with depressive symptoms. The role of social workers is essential so that depression screening can be accurately conducted.